Plant physiological and genetical aspects of the somatic embryogenesis process in conifers. Issue 5 (4th July 2019) - Egertsdotter, Ulrika
ABSTRACT: The processes for producing conifer planting stock by somatic embryogenesis (SE) in conifers are described. Implementation of SE presents opportunities and limitations at various stages of the in vitro process. The topic of genetic stability, or somaclonal variation, is a particular concern and reviewed. Following the in vitro processes, several factors affect the successful acclimation, early growth and field performance of SE planting stock. Experiences with other conifer species in the context of commercial production are reviewed. While SE production has historically been a very labor-intensive process, recent advances have been made to automate the various steps. Developments to enable SE for Norway spruce in Sweden are described.